THE INFLUENCE OF RELIGIOUS DEVOTION AND MENTAL HEALTH OF ISLAMIC EDUCATION STUDENTS AT UNIVERSITAS AHMAD DAHLAN - Rika Andriana; Nia Syam Nuri (International Journal of Teaching and Learning, 2026)
Students often forget their duties as servants, which has the potential to negatively impact their behavior patterns and trigger a lifestyle that disrupts mental health, whereas mental health arises from a personality capable of balancing the dimensions of life. This study aims to measure the extent of the influence of religious observance on the mental health of UAD students.The population of this study is PAI students at UAD. The data collection technique used was random sampling. The data collection technique uses a questionnaire. The data analysis technique used is simple regression analysis. This study shows a significant influence of religious observance on mental health, with regression results indicating a significance value of 0.00.Furthermore, the percentage of the influence of religious observance on mental health, obtained as an R Square value of 0.531, can be interpreted as religious observance contributing 53.1%. It also shows a correlation value of 0.728, indicating a strong relationship between religious adherence and mental health.